Ділова репутація підприємств як засіб забезпечення прибутковості на товарних ринках - Михальчишин, Н. Л. (Видавництво Львівської політехніки, 2015)
Обґрунтовано сутність ділової репутації як результату поведінки підприємства на ринку, належність до категорій, які сприймає та оцінює зовнішнє оточення. Визначено, що можливість здійснення певної поведінки суб’єктом господарювання зумовлюється його внутрішньою спроможністю, внутрішнім середовищем. Автор встановив, що діловій репутації притаманні матеріальні та нематеріальні прояви, через вплив на які можна завдавати шкоди та принижувати ділову репутацію. Визначено, що захист, підтримання та розвиток ділової репутації є необхідними засобами для забезпечення прибутковості підприємства. This article is justifying an essence of business reputation (“goodwill”) as a result of behavior of the enterprise on the market and it is determined that business reputation is one of categories that is perceived and evaluated by the surrounding entities that are in contact with a enterprise. It was established that business reputation depends on factors both, internal and external environments in which the entity operates. The business reputation is determined mostly by the internal environment, which in turn determines capabilities and level of performance in regards of enterprise's duties, and as a derivative – formation of reputation under the influence of the environment that shapes collective opinions and social assessment. In order to establish factors of the internal environment that shapes business reputation, it is required to find out what affects it's surroundings, as surroundings' public assessment will determine the reputation. External environment of the enterprise is formed by its customers, business partners (suppliers), competitors on the market (both actual and potential) and public authorities. Business reputation will depend on the ability of the Enterprise: provide high quality products; comply with the optimum ratio “price-quality”; save time for the consumer; provide consumers warranty, after-sales service and so on. Business reputation in a market economy depends on its consumer's satisfaction, and whether it is ready to conduct business with this particular supplier (customer retention). Accordingly, factors that can determine reputation in terms of suppliers is not only an ethical business component, but also the professionalism of the enterprise in the legal plane. In relations with competitors following factors of the business reputation are formed: pricing policy with consideration of market trends; ability to influence the market size of the goods; respect for the integrity of competition and so on. Based on the results of studies of the internal environment may be determined that business reputation will be formed by the personnel's potential. Formation of the enterprise's reputation can be in line or can diverge in time with different stages of the life cycle of the enterprise. The paper found that business reputation may have tangible and intangible manifestations, the influence of which can cause damage to business reputation. It is also is determined that business reputation cannot be related to structural categories and cannot include components because it is moral and ethical category. It should be borne in mind that business reputation is influenced by numerous factors of internal and external environments. It is determined that in addition to the cost of improving and maintaining business reputation, enterprise should include the costs of its protection, which depend on the chosen protection method, and to ensure profitability of enterprise business reputation should be protected, maintained and improved.
The business reputation of enterprises as a means of profit in trading markets
Keywords: ділова репутація; зовнішнє середовище; внутрішнє середовище; фактори; морально-етична категорія; нематеріальний актив; захист; business reputation; external environment; internal environment; factors; moral and ethical category; non-material active; protection